A Case Study Investigation of Year 8 Students' Experiences with Online Learning Through the Padlet App in a State-Maintained Girls' Grammar School. Issue 46 (2022) - Cleary, Caolain J.
Abstract: If the past two years have proven anything, it is that students today hold a tremendous capacity to adapt to incredibly difficult learning environments. This paper explores student learning experiences in one such learning environment, the period of online learning that occurred between January and March 2021 due to COVID-19-related school closures. Investigating the effectiveness of the digital learning platform Padlet in terms of student engagement with the Latin curriculum and its cultivation of Latin comprehension skills, this case study of Year 8 students in a state-maintained girls' grammar school demonstrates the value of collaborative, discussion-based approaches to remote teaching. The value of digital learning platforms in our post-pandemic educational environment is demonstrated in its potential to bridge the communicative gap felt by many students when taught online, simulating the lively classroom climate which so often generates exciting and effective learning opportunities for each student. As this paper demonstrates, digital learning platforms hold the potential not only to assist educators in coping with the challenges of remote learning, but also to extend student learning in ways once considered unimaginable beyond the realms of the physical classroom. As a result, this paper argues that the position of such platforms in the post-pandemic classroom must be advocated and supported further.